Prediction of strong-motion seismic movements in Portugal – an approach based in the finite-difference method - Torres, R. (2012)
The goal of the research plan is to contribute to an improved assessment of the seismic hazard in the Lower Tagus Basin (L.T.B.), in order to achieve that, we propose the introduction of realistic methods on the prediction of ground motion produced by moderate to large earthquakes in this area. This process involves the establishment of a structural 3D model and the evaluation of seismic potential of the faults in the studied area. The method employed involves modeling based in Finite difference Methods (FDM), done on a massive parallel computing system. There is already a 3D velocity model (SWIBMOD2006 model and VFGEN program [1]) and a methodology for wave propagation of the SW of Portugal which is based on the Finite difference method and applied through the E3D program. The work we are currently developing is based in the previous model but applied to the Tagus valley with greater resolution. With that model we hope to contribute to a better evaluation of the seismic hazard and seismic risk in the L.T.B. Besides this seismological interest, we hope to contribute to understand the sedimentary and tectonic evolution of the Mesozoic Lusitanian and Cenozoic Lower Tagus Basins. In PGUE we will present the new velocity model and the results of the modeling to different seismic scenarios.